2009
DOI: 10.2215/cjn.03330509
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil Count Is Positively Correlated with Albumin Excretion Rate in Men with Type 2 Diabetes

Abstract: Background and objectives: Patients with allergic disorders such as allergic rhinitis or asthma have been reported to be at increased risk for atherosclerosis. In this study, we evaluated the relationships between peripheral eosinophil count and degree of albumin excretion rate, which is a useful marker of cardiovascular mortality as well as diabetic nephropathy in patients with type 2 diabetes.Design, setting, participants, & measurements: We evaluated relationships of peripheral eosinophil count to degree of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 20 publications
1
30
1
Order By: Relevance
“…IL-5 is a T H 2 homodimeric cytokine involved in the differentiation, maturation, migration, development, survival, trafficking and effector function of blood and local tissue eosinophils, in addition to basophils and mast cells [35]. A recent study reported a potential link between IL-5 actions and diabetic nephropathy, since eosinophil count was positively correlated with albumin excretion rate in men with T2D [36]. Moreover, an 8-year prospective cohort analysis of 1327 Chinese patients with T2D reported that polymorphisms in the IL-5 receptor α subunit correlated with ischemic stroke [37].…”
Section: Discussionmentioning
confidence: 99%
“…IL-5 is a T H 2 homodimeric cytokine involved in the differentiation, maturation, migration, development, survival, trafficking and effector function of blood and local tissue eosinophils, in addition to basophils and mast cells [35]. A recent study reported a potential link between IL-5 actions and diabetic nephropathy, since eosinophil count was positively correlated with albumin excretion rate in men with T2D [36]. Moreover, an 8-year prospective cohort analysis of 1327 Chinese patients with T2D reported that polymorphisms in the IL-5 receptor α subunit correlated with ischemic stroke [37].…”
Section: Discussionmentioning
confidence: 99%
“…Defining the regulation of inflammatory pathways and metabolic signals is a complex problem to undertake, yet individual findings in clinical studies 58 and use of animal models 59 have suggested a potential role for eosinophils in maintaining metabolic homeostasis. In particular, studies in mice have highlighted a role for eosinophils 59 in modulating adipocyte tissue macrophages, which are important in metabolic homeostasis.…”
Section: Metabolic Syndrome: Adipose Insulin and Inflammationmentioning
confidence: 99%
“…Eosinophils are potent effector cells in the pathogenesis of many disorders, ranging from allergy and bronchial asthma 1, to eosinophilic esophagitis 2, colitis ulcerosa 3, hypereosinophilic syndrome 4, and renal disease 5. Activated eosinophils are one of the primary sources of cytotoxic proteins, proinflammatory cytokines, and growth factors, such as IL‐4, IL‐5, IL‐10, and IL‐13 6, and promote numerous immunoregulatory functions that lead to the progression of inflammation, mucus secretion, tissue remodeling, and angiogenesis 7.…”
mentioning
confidence: 99%